Green technologies for industrial waste remediation - Mathuriya, Abhilasha Singh; Pandit, Soumya; Singh, Neeraj Kumar (Environmental science and engineering, 2023)
This proposed book chapter is expected to provide the readers with wide aspects of green technologies for industrial waste remediation. The first chapter is dedicated to the introduction to the title of the book. The chapter discusses various green technologies for industrial waste remediation. After that, the second chapter emphasizes the different types of applications of microorganisms in industrial waste treatment.